Decolonising Islamic Legal Authority beyond Sharīʿah Courts: A Socio-Legal Study of Singapore - Nadiyah N. Shahab; Khadeejeh Alrawashdeh; Ayaka M. Hinata (Indonesian Journal of Islamic Law, 2026)
This article critically re-examines Islamic legal authority in postcolonial Singapore by challenging the prevailing assumption that the vitality of Islamic law depends on the institutional expansion of Sharīʿah courts. Drawing on socio-legal analysis and postcolonial legal theory, it argues that court-centred and state-centric models—rooted in colonial legal rationality—have narrowed the conceptualisation of authority, normativity, and reform in contemporary Muslim contexts. Rather than treating Singapore as a deficient case due to its limited Sharīʿah jurisdiction, the study repositions it as a theoretically productive site for analysing how Islamic legal authority operates beyond formal adjudication. The findings show that authority in Singapore is not diminished but reconfigured through a dispersed and relational framework encompassing bureaucratic governance, ethical reasoning, community mediation, and discursive practices. This configuration reveals that colonial epistemologies continue to privilege institutional visibility while obscuring non-judicial modes of normativity that remain central to lived Islamic legal practice. By decentring courts as the primary locus of Islamic law, the article advances a conceptual reorientation of authority as a negotiated and socially embedded process rather than a fixed institutional attribute. In doing so, the study contributes to debates on decolonising Islamic law by demonstrating that legal reform in the Global South requires not the expansion of religious courts but a critical rethinking of the epistemic foundations through which authority, legitimacy, and legal meaning are constructed within plural legal orders.